Craigslist online community - Robinson, David, (SAGE Knowledge. Cases., 2017)
Online community, "CRAIGSLIST" was an early winner on the Internet, but by 2001, the pioneer was running out of money and facing the problem of how to charge for services that users had come to expect for free. In July 2001, Craig Newmark, CEO and founder of CRAIGSLIST, asked his loyal users to help the popular community website to come up with a plan to save it from running out of money.